Harnessing the potential of chloroplast-derived expression elements for enhanced production of cellulases in Escherichia coli - Ayesha Siddiqui; Muhammad Mudassar Iqbal; Asad Ali; Iqra Fatima; Hazrat Ali; Aamir Shehzad; Sameer H. Qari; Ghulam Raza; Muhammad Aamer Mehmood; Peter J. Nixon; Niaz Ahmad (PeerJ)
Thermophilic cellulases can play a crucial part in the efficient breakdown of cellulose—a major component of lignocellulosic plant biomass, however, their commercial production needs simple and robust biomanufacturing biosystems. In this study, two cellulases (β-glucosidase and endoglucanase) were heterologously expressed in Escherichia coli under a chloroplast-derived constitutive promoter and expression-enhancing terminator. The genes encoding the cellulases were sourced from a thermophilic bacterium Thermotoga maritima to exploit their industrially needed thermotolerance potential. The codon-optimized gene sequences were synthesized and placed under a tobacco chloroplast 16S rRNA promoter (Prrn), along with the 5′ UTR (untranslated region) from gene 10 of phage T7 (T7g10). A six-residue long histidine tag (His6-tag) was attached to the N-terminus for protein detection. A high-level of expression of β-glucosidase and endoglucanase in E. coli was recorded from the chloroplast promoter and terminator. Furthermore, the activity assays confirmed that the recombinant enzymes maintained their activity at elevated temperatures. Thermostability analysis showed that recombinant enzymes retained their thermotolerance even after being expressed in a non-native host. Where, β-glucosidase and endoglucanase showed their optimum activities at 90 °C and 100 °C, respectively. Examination of the 3D structures of T. maritima cellulases revealed differential ionic interactions contributing to this high degree of thermotolerance. The study highlights the feasibility of producing thermostable versions of recombinant enzymes in E. coli at high levels. Our finding underscores the potential of this approach to meet industrial demands for efficient enzyme production employing E. coli as a robust biomanufacturing platform.